34 Exploring the feasibility and effectiveness of a novel community based programme for cardiac rehabilitation in the west of ireland. (16th October 2019) - Dunne, D; Keegan, D; Gibson, I; Seery, S; Harris, A; Hall, P; Crowley, J
Abstract : Background: With the prevalence of coronary heart disease increasing globally it is imperative that we explore alternative methods of delivering cardiac rehabilitation (CR) to improve patient outcomes in accordance with national and international CR guidelines. This study examines the feasibility and effectiveness of delivering a community based CR programme on medical and lifestyle risk factor management in the west of Ireland. Methods: Patients with coronary heart disease; meeting the inclusion criteria for referral to CR were invited to attend a 12- week CR programme consisting of a professional multi-disciplinary (nurse, dietitian, physiotherapist) lifestyle intervention, with appropriate risk factor and therapeutic management delivered within a community setting. Risk factors such as blood pressure, lipids, smoking, BMI (body mass index), waist circumference and estimated MET max were assessed at baseline and end of programme (EOP). Results: 255 patients enrolled in the CR programme. Mean age of the participants was 66.6 yrs, 72.9% were male and 35.4% had previous cardiac history. The programme adopted an integrated approach to care and in addition to cardiac patients it included a cohort of Stroke (17%) and Peripheral Vascular Disease (PVD) (4%) patients. Outcome data on 196 patients who completed the 12 week programme were analysed (table 1). Conclusions: Data from this multi-component comprehensive community based CR programme suggest that the management of CR patients can be successfully integrated and delivered within a community setting by a specialist multi-disciplinary team (MDT). This study has demonstrated improvements in patient outcomes across biomedical, anthropometric and lifestyle risk factors. Benefits were also noted in the psychosocial health and wellbeing of the participants including improvements in quality of life (QoL) measures.